Agronomical evaluation of cape gooseberries (physalis peruviana l.) from central and north-eastern colombia (2012)
The aim of the present study was to evaluate agronomical traits in a germplasm collection of cape gooseberry from central and north-eastern Colombia in order to measure the variability of the collection in relation to the geographic origin of the accessions and their biological status (cultivated, feral and undetermined). For this purpose, a total of 54 accessions from the departments of Norte de Santander, Santander, Boyacá and Cundinamarca was evaluated using 30 descriptors (23 quantitative and seven qualitative) by means of a principal component analysis (PCA) applied to the quantitative variables and a multiple correspondence analysis (MCA) applied to the qualitative variables. The first two PCA components explained 52.42% of the total variation. The first component (39.79%) was positively related to the weight and fruit size and negatively to the pH and maturity index. A hierarchical classification analysis based on the continuous variables resulted into two classes with contrasting affinities, with 94.37% of the cultivated accessions grouped into class 2 and 64% of the undetermined accessions grouped into class 1. The first three MCA axes explained 48.48% of the total variation. The first one (20.51%) was related to strong serosity, medium fruit size and absence of damage caused by Phoma sp. A hierarchical classification analysis based on the categorical variables resulted in four classes (A, B, C, and D); with one of them (class B) containing five accessions characterized by having strong serosity and absence of damage caused by insects and pathogens.